The Preferences of Student’s Learning Method Based on Course, Gender and Age: Visual, Audio, Reading & Kinesthetic (VARK) - Dzulkalnine, Natasha; Sumardi, Nur Athirah; Azman, Mohamed Nor Azhari; Ibrahim, Ihfasuziella; Qudus, Nur; Abu Bakar, Syarifah Mastura Syed (Information Management and Business Review, 2024)
Different students have different preferences for learning methods. Some of the students might prefer visual or audio reading or kinesthetic learning. It is believed that the student’s preferences of learning methods might help the students understand more about the subject and hence contribute to their academic performance. Therefore, this study investigates whether the students’ preferences for learning methods are influenced by the courses they registered for and the gender, and age of the students. A sample of 341 students from different backgrounds was selected in this study comprised of students from the Faculty of Business and Management, Faculty of Accountancy, Faculty of Graphic Design, and Faculty of Nursing in Universiti Teknologi MARA (UiTM) Puncak Alam. The findings show that course and gender play an important role in student’s preferences for learning methods while age is not the significant variable. There is a very high positive correlation between courses and preferences of learning methods, while age and gender have a high positive correlation toward preferences of learning methods. This study might help educators in tailoring their lectures to the students’ preferences of learning methods, thus contributing to the academic performance of the students.